THE IMPACT OF FINANCIAL BEHAVIOURS ON FINANCIAL WELL-BEING AMONG STUDENTS IN UITM KELANTAN - Siti Nur Zahirah Omar; Sarah Azereen Che Halib; Nur Nadhirah Azman; Syamil Nafisz Sahrul; Ahmad Hariz Salahuddin; Muhammad Irfan Mohd Afandi (International Journal of Accounting, Finance and Business, 2024)
This study explores the intricate relationship between financial behaviors and financial well-being among students at University Technology MARA (UiTM) Kelantan. The research aims to investigate the impact of financial literacy, self-control, financial socialization, and saving behavior on the financial well-being of 384 respondents. The study employs a quantitative approach, utilizing survey data to analyze the interplay between the dependent variable, Financial well-being, and the independent variables, namely Financial Literacy, Self-Control, Financial Socialization, and Saving Behaviour. The findings of this research contribute to the existing body of knowledge on financial well-being among students, providing insights into the specific factors that influence their financial situations. By examining the role of financial literacy, self-control, financial socialization, and saving behavior, this study seeks to inform policymakers, educators, and financial institutions about the key determinants that can enhance the financial well-being of students at UiTM Kelantan.